The Metro Manila Greenprint 2030 : Building a Vision - Metropolitan Manile Development Authority; World Bank (World Bank, Washington, DC, 2015)
The Greenprint 2030 is a resolute attempt on the part of MMDA to engage all stakeholders in a process to create a common vision for the region’s future. For the first time, all 16 cities and one municipality comprising Metro Manila are linked under one vision that sets developmental priorities for the region and provides direction to achieve those priorities. The vision is formulated within the wider Mega Manila context, considering the shared challenges and opportunities with adjacent provinces. Like other metropolitan plans, Greenprint 2030 starts with a vision. However, it differs from the comprehensive metropolitan planning exercises in that it focuses on developing strategic areas of opportunity. Through the vision process, connectivity, inclusiveness, and resilience emerged as the key entry points for strategic engagement. Based on the vision the Greenprint 2030 will provide metropolitan wide spatial guidance, demonstrate coordination mechanisms, and identify areas for catalytic investments. The green in Greenprint goes beyond trees and open spaces green is efficient transportation, affordable housing, and more resilient infrastructure. It emphasizes sustainable urban development as the underlying principle across the three themes of inclusivity, connectivity, and resiliency. These sectors work together to enable more efficient use of resources and to create a livable urban environment. The Greenprint 2030 offers the strategic direction which informs comprehensive spatial and development plans prepared by national and local government agencies, related to Metro and Mega Manila. Through this process, more options for metropolitan governance will also be examined. The aim is to equip the metropolitan area to compete globally and to provide its citizens a safe, resilient, and green environment.